Correlating serum micrornas and clinical parameters in amyotrophic lateral sclerosis. Issue 2 (25th March 2018) - Raheja, Radhika; Regev, Keren; Healy, Brian C.; Mazzola, Maria Antonietta; Beynon, Vanessa; Von Glehn, Felipe; Paul, Anu; Diaz‐Cruz, Camilo; Gholipour, Taha; Glanz, Bonnie I.; Kivisakk, Pia; Chitnis, Tanuja; et al.
ABSTRACT: Introduction : Amyotrophic lateral sclerosis (ALS) is a debilitating neurologic disorder with poor survival rates and no clear biomarkers for disease diagnosis and prognosis. Methods : We compared serum microRNA (miRNA) expression from patients with ALS with healthy controls and patients with multiple sclerosis and Alzheimer disease. We also correlated miRNA expression in cross‐sectional and longitudinal cohorts of ALS patients with clinical parameters. Results : We identified 7 miRNAs (miR‐192‐5p, miR‐192‐3p, miR‐1, miR‐133a‐3p, miR‐133b, miR‐144‐5p, miR‐19a‐3p) that were upregulated and 6 miRNAs (miR‐320c, miR‐320a, let‐7d‐3p, miR‐425‐5p, miR‐320b, miR‐139‐5p) that were downregulated in patients with ALS compared with healthy controls, patients with Alzheimer disease, and patients with multiple sclerosis. Changes in 4 miRNAs (miR‐136‐3p, miR‐30b‐5p, miR‐331‐3p, miR‐496) correlated positively and change in 1 miRNA (miR‐2110) correlated negatively with changes in clinical parameters in longitudinal analysis. Discussion : Our findings identified serum miRNAs that can serve as biomarkers for ALS diagnosis and progression. Muscle Nerve 58 : 261–269, 2018